Über die Braunlehmrelikte des Atakor: (Hoggar-Gebirge, Zentral-Sahara) - Kubiëna, Walter L. (ERDKUNDE, 1955)
1. In the High Atakor, Central Sahara, a subtropical layer of brown loam has been preserved which, despite the present desert climate, has remained practically unchanged. 2. In the paper a comparison is made between remains of brown loam, which mostly occur on basalt, and soils formed from basalt during recent times. Those used for comparison are mainly the following: the tropical brown loams of Fernando Poo (Gulf of Guinea), the brown earths of Middle Europe and Northern Europe, the meridional brown earths of Central Spain and the Canary Islands, the recently formed soils of the Sahara and the high mountain desert of the Teide (Teneriffe). At the same time soils that have developed under known climatic changes from brown earths remains are drawn upon for comparison. 3. By means of analysing the profile morphology, micromorphology and the way in which a change of minerals had occurred, it was found that the brown loam remains are soil formations that took place during a pronounced humid subtropical to tropical climate. 4. In addition to the brown loam remains, there are further fossil red loams which in almost all cases are covered by basalt sheets and thus in comparison with the brown loams are easily recognised as being of greater age. By comparative investigation of basalt red loams of other areas, it can be stated that they are soils formed under a humid tropical climate with pronounced hot dry-periods. The red loams are of differing degrees of maturity; their degree of laterization is small. 5. The time when the brown loam cover was formed was most likely the latest great Pluvial period, since in humidity this by far surpassed the later only moderately humid periods. 6. The reason why the brown loam remains have changed so little is to be found in the fact that the desert climate in the High Atakor is of relatively recent date and further that at this altitude it is less extreme and its consequences are also less pronounced. After the tropical rain climate of the last Pluvial period humid climates followed which, though not allowing the formation of brown loam profiles of the extreme type (Matadero-Variant), as found here, nevertheless facilitated their preservation. 7. The fossil red loams are clearly older than the brown loams but very likely are still of Pleistocene age. According to the results of the paleo-pedological investigations this time must also be postulated for the volcanism itself, since a recent age cannot be assumed for the soil formations which accompany it.